Diseases of Peach Caused by Ascomycete Fungi in Fergana Valley - Kamaldinovich, Karimov Otabek (American Journal of Biodiversity, 2025)
The distribution and development of peach diseases were studied during field observations conducted in some regions of the Fergana Valley. It was found that leaf curling was the most common disease in peach trees in orchards. Symptoms of the disease appeared in early spring, and in summer, with an increase in temperature and a decrease in air humidity, its development stopped. In peach trees, clasterosporiosis was rare, powdery mildew was very rare, and moniliosis was not recorded.